Mind, soul, and consciousness: religion, science, and the psy disciplines in modern South Asia. Issue 3 (3rd July 2018) - Harding, Christopher
ABSTRACT: This introductory article lays out some of the key intellectual, therapeutic, political, and social concerns where religion, science, and the psy disciplines have come together – including what we 'do' with our experience of the world, and of ourselves; the means we choose to use in ordering our thoughts and emotions; the language(s) we deploy in doing so; and the authorities we look to for guidance. Short introductions are offered along the way to the work of scholars in this emerging field including Ashis Nandy and Nikolas Rose, alongside illustrative comparisons drawn from the Indian and Japanese contexts in the modern era. These latter span a range of concerns: the extension of interventionist ambitions by the modern state to include the utilization of the psy disciplines – theories, practitioners, institutions; the appearance of language associated with these disciplines in everyday life, sometimes using the health of individuals as a putative barometer of society's health more broadly; and the power of entrepreneurial individuals to steer these disciplines in personalized directions, thanks both to their relative newness and the liminal nature of their subject matter. The chapter goes on to offer a survey of the articles featured in this special issue of South Asian History and Culture, contextualizing them and laying out the principal aims of the issue.